Integrated natural sciences approaches to the protection of medieval ruins - Jakub Novotný; Jiří Bláha (Ochrona Dziedzictwa Kulturowego, 2020)
The aim of this paper is to present the Report of innovative restoration techniques, technologies and materials used in conservation in the context of natural sciences and heritage science of the RUINS Project. First, the specifics of preservation and maintenance of ruins are briefly described. Subsequently, the context of natural sciences and the new scientific discipline of heritage science, including the link to innovation, are indicated. The paper then presents the structure of the report and an example of one record representing one specific technique. Record structure is ready to be transferred to versatile data set so it could be converted into an updatable online database in the future.